Group Guidance of Mind Mapping to Improve Critical Thinking Skills - Lestari, Rahayu; Wibowo, Mungin Eddy; Awalya, Awalya (Jurnal Bimbingan Konseling, 2020)
This study attempted to examine the effectiveness group guidance of mind mapping to improve critical thingking skills. The study used pre-test and multiple post test method. The subjects in this study were eight students of grade tenth from Vocational Public High School (SMK, Sekolah Menengah Kejuruan) Negeri 2 Semarang. The data collection process utilized critical thinking scale targeting on six aspects, they are: interpretation, analysis, evaluation, conclusion, explanation, and self-regulation. The analysis used repeated measure ANOVA. The results showed the significant increase in critical thinking (F2.14 = 74.66 p < 0.01). The finding of this study confirmed that the group guidance of mind mapping is effective in improving critical thinking skills of students in SMK Negeri 2 Semarang.